1988
DOI: 10.23986/afsci.72339
|View full text |Cite
|
Sign up to set email alerts
|

Response of silage intake and milk production to replacement of barley by barley fibre derived from integrated starch-ethanol process

Abstract: Abstract. A duplicated 4x4 Latin Square experiment was conducted to determine the effects of a gradually increased level of barley fibre in the diet on ad libitum grass silage intake and milk production. Barley fibre is a fibrous ethanol-starch by-product (120 g crude protein, 550 g neutral detergent fibre (NDF) and 120 g starch/kg dry matter (DM)). The four supplements, given at the rate of 6.5 kg/d on DM basis, were barley (B) and barley of which 333 g/kg (BF), 667 g/kg (FB) and 1000 g/kg (F) were replaced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
1
5
1
Order By: Relevance
“…Replacing barley grain with BF in the diet had an effect on the OM digestibility similar to that observed by Huhtanen (1992) in growing bulls and by Huhtanen et al (1988) in dairy cows. The reduction in NDF digestibility, when replacing barley grain with BF, was partly a consequence of decreasing proportion of silage's NDF in the total NDF intake.…”
Section: Effect Of Energy Sourcesupporting
confidence: 68%
“…Replacing barley grain with BF in the diet had an effect on the OM digestibility similar to that observed by Huhtanen (1992) in growing bulls and by Huhtanen et al (1988) in dairy cows. The reduction in NDF digestibility, when replacing barley grain with BF, was partly a consequence of decreasing proportion of silage's NDF in the total NDF intake.…”
Section: Effect Of Energy Sourcesupporting
confidence: 68%
“…For the S treatment, no difference in silage DMI between concentrates was noticed, but for the F treatment the silage intake was lower with the more fibrous concentrate B than A. Contrary to our results, Ala-Seppä lä et al (1988), Huhtanen et al (1988) and Aston et al (1994) measured increased silage intake when starchy concentrates were replaced by more fibrous concentrates. In these earlier studies the concentrate was given twice a day, whereas in our study the concentrate was given from computerized concentrate feeders during five feeding periods.…”
contrasting
confidence: 99%
“…Impaired gain of BF75 bulls was a consequence of decreased DM and energy intake, which was possibly partly caused by decreased OM digestibility (OMD). Replacing barley grain with BF in the diet affected the OMD similarly as observed by Huhtanen (1992) in bulls and by Huhtanen et al (1988) in dairy cows. Barley fibre contains much more NDF and less starch than barley grain, and the difference in OMD can be attributed to a lower digestibility of cell wall components of BF than of those of barley starch.…”
Section: Discussionmentioning
confidence: 53%
“…Therefore the bulls could increase DMI when the energy content of the rations decreased with BF25 and BF50 diets compared with the control. In addition, replacing starch with fibrous concentrate may change rumen fermentation by increasing rumen pH, resulting in more efficient cellulolysis in the rumen, especially with high concentrate proportions (Huhtanen et al 1988), which may partly explain the increased DMI observed with the BF25 and BF50 diets compared with the control. However, DMI decreased when 75% of the barley grain concentrates was replaced with BF, so on the BF75 diet the bulls could not compensate the lower energy content of TMR by increasing DMI.…”
Section: Discussionmentioning
confidence: 99%